Influence of the use of social media on patients changing dental practice: a web-based questionnaire study - Yolanda Freire; Margarita Gómez Sánchez; Ana Suárez; Gerardo Joves; Marlen Nowak; Víctor Díaz-Flores García (BMC, 2023)
Abstract Background Recent years have seen an increase in the use of social media, by the healthcare sector, including dentistry. Indeed, social media may now be important communication tools for dental practices and patients. This work analyzes the influence of patient (male and female) use of dental practice social media on their decision to change practice. The results also provide insight into the factors patients considered important when choosing a dental practice. Methods This study was approved by the Ethics Committee of the Universidad Europea de Madrid (No. CIPI/22.022). Using a web-based questionnaire, a cross-sectional study was undertaken involving a Spanish population that made use of dental services. The questionnaire consisted of four parts covering provision of informed consent, the collection of sociodemographic data, patient use of dental practice social media, and the factors considered important when changing dental practice. Results All participants gave their informed consent regarding inclusion. No compensation was provided for participation. 588 people responded to the questionnaire, of whom 503 were eligible for inclusion. Most respondents were female (312/503; 62%). Most (151/503; 30%) last changed dental practice during the previous 2-5 years. 208/503 (41.4%) indicated that they had visited dental practice social media. 118/503 (23.5%) indicated that they had made use of such the last time they changed dental practice; 102 of these 118 (85.6%) reported their experience to have influenced their decision to change. Respondents who had changed practice in the last 5 years had interacted with dental practice social media more than those who changed over 11 years ago (p < .05), and those who changed practice in the present/past year were more influenced by these media (p < .05). The factor considered most important was 'Facilities and technology'. No gender-based differences were seen for any measured variable (p < .05). Conclusions Different factors affect the selection of a new dental practice, but respondents who changed practice in the last few years were more likely to have made use of dental practice social media, which, for some, influenced their final decision to change. Dental practices might do well to consider using social media as communication and marketing tools.